Between squares and monuments, silence and erasure: an analysis of the inexistence of Xavante references in Barra do Garças (Mato Grosso, Brazil): Between squares and monuments, silence and erasure: an analysis of the inexistence of Xavante references in Barra do Garças (Mato Grosso, Brazil) (Revista de História da UEG (REVHIST), 2025)
This article analyzes the symbolic silencing and erasure of Indigenous presence, particularly which of the Xavante people, in the urban context of Barra do Garças, Mato Grosso, based on the concepts of coloniality and the selective construction of memory. It is understood that the exclusion of Indigenous peoples from the city's official narrative does not stem from a physical absence, given that over 4,000 Indigenous individuals live in the municipality, but rather constitutes a historical process of symbolic denial, perpetuated through folklorized representations, selective monuments, and hegemonic discourses. The research reveals that the urban space privileges symbols such as the colonizer, the gold miner, and even extraterrestrials, relegating the Xavante to oblivion. This erasure is shown to be embedded in a still-active colonial logic that denies Indigenous peoples their rights to memory, voice, and belonging. The study concludes that recognizing and valuing the Xavante culture and history is fundamental to reconstructing a more just, plural, and decolonial local identity. The research uses dialectical methodology, based on historical, bibliographical and documentary analysis, resorting to direct observation in the urban space researched.Keywords: silencing; erasure; Xavante people; Barra do Garças, MT.
Keywords: Silencing; Erasure; Xavante people; Barra do Garças, MT